Vector control for the Chikungunya disease - Yves Dumont; Frederic Chiroleu (Mathematical Biosciences and Engineering)
We previously proposed a compartmental model to explain the outbreak ofChikungunya disease in Réunion Island, a French territory in Indian Ocean,and other countries in 2005 and possible links with the explosive epidemicof 2006. In the present paper, we asked whether it would have been possibleto contain or stop the epidemic of 2006 through appropriate mosquito controltools. Based on new results on the Chikungunya virus, its impact on mosquitolife-span, and several experiments done by health authorities, we studiedseveral types of control tools used in 2006 to contain the epidemic. Wepresent an analysis of the model, and we develop a new nonstandard finite differencescheme to provide several simulations with and without mosquito control. Ourpreliminary study shows that an early use of a combination of massivespraying and mechanical control (like the destruction of breeding sites) canbe efficient, to stop or contain the propagation of Chikungunya infection,with a low impact on the environment.